Cortrak feeding tube placement: accuracy of the 'GI flexure system' versus manufacturer guidance. (26th November 2020) - Taylor, Stephen; Manara, Alex; Brown, Jules; Sayer, Kaylee; Clemente, Rowan; Toher, Deirdre
Abstract : Electromagnetic (EM) guided enteral tube placement may reduce lung misplacement to almost zero in expert centres, but more than 60 undetected misplacements had occurred by 2016 resulting in major morbidity or death. Aim: Determine the accuracy of manufacturer guidance in trace interpretation against what is referred to as the 'GI flexure system'. Methods: The authors prospectively observed the accuracy of the 'GI flexure system' of trace interpretation against manufacturer guidance in primary nasointestinal (NI) tube placements. Findings: Contrary to manufacturer guidance, 33% of traces deviated >5 cm from the sagittal midline and 26.5% were oesophageal when entering the lower left quadrant, incorrectly indicating lung and gastric placement, respectively. Conversely, the GI flexure system identified ≥99.4% of GI traces when they reached the gastric body flexure; 100% at the superior duodenal flexure. All lung misplacements were identified by the absence of GI flexures. Conclusion: Current manufacturer guidance should be updated to the GI flexure system of interpretation.